2014
DOI: 10.1016/j.eneco.2013.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Energy intensity: A decomposition and counterfactual exercise for Latin American countries

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(41 citation statements)
references
References 37 publications
4
34
0
1
Order By: Relevance
“…As already mentioned, this effect is relatively small on average, but one needs to bear in mind that a country's standard of living is also incorporated in several other explanatory variables of the model and this estimate is thus the direct, net effect of GDP per capita on energy intensity. This result is in accordance with the mentioned studies [10,11] and confirms that income reflects the level of economic development, which is closely related to energy efficiency improvements. Generally speaking, economically developed countries have competitive industries and a high level of specialisation in technology development sectors.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…As already mentioned, this effect is relatively small on average, but one needs to bear in mind that a country's standard of living is also incorporated in several other explanatory variables of the model and this estimate is thus the direct, net effect of GDP per capita on energy intensity. This result is in accordance with the mentioned studies [10,11] and confirms that income reflects the level of economic development, which is closely related to energy efficiency improvements. Generally speaking, economically developed countries have competitive industries and a high level of specialisation in technology development sectors.…”
Section: Resultssupporting
confidence: 92%
“…On the other hand, as income broadly reflects the stage of development, it is expected that it would reduce energy intensity as both households and producers use more energy-saving and more efficient technologies. Empirical analysis based on 75 countries in the period 1971e2010 showed that energy intensity declines as income increases [10]. Measuring energy intensity and its determinants in China's regional economies [11], the research showed that energy efficiency improves as income per capita rises.…”
Section: Introductionmentioning
confidence: 99%
“…Wang [42] decomposed energy intensity changes into five components (technological catch-up, technological progress and changes in capital -energy ratio, labor -energy ratio and output structure) and concluded that ''technological progress, capital accumulation and output structure change contributed to the declines of energy intensity from 1980 to 2010'' [42: 482]. Other researchers also came to similar conclusions using decomposition analysis: energy intensity depends on technological energy efficiency [39,[43][44][45]. But what implications for enhancing technological energy efficiency can be deduced from these conclusions?…”
Section: Energy Intensity Datamentioning
confidence: 96%
“…While the empirical exercise in Voigt et al (2014) seems the most exhaustive in its genre, most of the literature that uses SDA focuses on a small number of countries or emissions types, and many examine China vis a vis the US. For instance, (Mulder and de Groot, 2012) and (Mulder et al, 2014) (Su and Ang, 2012) and (Tian et al, 2014)) the US and the EU27 ; (Poudel et al, 2009), (Russi et al, 2008) and (Jimenez and Mercado, 2014) present evidence on LAC s; while (Panayotou et al, 2000) on a number of developing countries. Although the body of evidence based on SDA conducted on a large number of countries is smaller that evidence on single macro-regions, we can examine the case of the LAC s, which is particularly interesting due to their main specialisation in natural resources.…”
Section: Decomposition Evidence: Sectoral Structure and Technical Changementioning
confidence: 99%